"Love is only between living beings who are equal in power": On what is alive (and what is dead) in Hegel's account of marriage. (10th December 2018) - Katz, Gal
Abstract: The paper develops a conception of marital love as a complex recognitive relation, which I articulate by juxtaposing it against other recognitive relations that figure in Hegel's theory of modern civil society (i.e., respect and esteem). Drawing on Hegel's early writings, I argue that, if love is to provide its unique sort of recognition, it must obtain between "living beings who are equal in power"—a peculiar form of equality that I name (drawing on Stanley Cavell's work) "dynamic equality." I conclude that it is by Hegel's own lights that we should reject his notorious conception of the sexual difference. However, I also offer reasons why, from Hegel's early 19th century perspective, he could consider the following two conditions as compatible: (1) equality within marriage and (2) sexual hierarchy outside marriage, namely, in civil society.